A comparative study on microstructure, nanomechanical and corrosion behaviors of AlCoCuFeNi high entropy alloys fabricated by selective laser melting and laser metal deposition. (20th December 2022) - Ren, Yaojia; Wu, Hong; Liu, Bin; Liu, Yong; Guo, Sheng; Jiao, Z.B.; Baker, Ian
Highlights: Hierarchically heterogeneous microstructures exist in both SLM- and LMD-processed specimens. Core-shell FCC precipitates in LMD bear {110} texture at high surface energy and high strain energy. Hot cracks occurred in both types of specimens due to the incompletely suppressed cu segregation. A correlation mechanism between microstructure, nano-mechanics, and corrosion behavior was obtained. Abstract: The present study investigated the microstructure, nanomechanics, and corrosion behavior of AlCoCuFeNi high entropy alloys fabricated by selective laser melting (SLM) and laser metal deposition (LMD). The microstructure of SLM-processed specimens was mainly composed of columnar-grained BCC matrix (∼90 µm in width) and Cu-rich twinned FCC phase. The columnar grains grew epitaxially along the building direction and exhibited a strong {001} texture. In comparison, a coarse columnar-grained BCC matrix (∼150 µm in width) with a stronger 〈001〉 texture, rod-like B2 precipitates, and large core-shell structured FCC phases were formed in the LMD-processed specimens due to the higher heat accumulation effect. Consequently, the LMD-processed specimens showed a lower hardness, wear resistance, and corrosion resistance, but higher creep resistance and reduced Young's modulus than the SLM-processed specimens. Hot cracks occurred in both types of specimens, which could not be completely suppressed due to Cu segregation.